2020
DOI: 10.1002/anie.201914271
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Assisted Homolytic Dissociation of Propyne on a Reduced Ceria Surface

Abstract: The emergence of ceria (CeO2) as an efficient catalyst for the selective hydrogenation of alkynes has attracted great attention. Intensive research effort has been devoted to understanding the underlying catalytic mechanism, in particular the H2–CeO2 interaction. Herein, we show that the adsorption of propyne (C3H4) on ceria, another key aspect in the hydrogenation of propyne to propene, strongly depends on the degree of reduction of the ceria surface and hydroxylation of the surface, as well as the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Additionally, the rate-determining step or possible reaction pathway of reactions over CeO 2 -based catalysts can be identified by the reaction energy profiles via theoretical calculations. ,,,,, For example, during the oxidation of (5-(1,3-dioxan-2-yl) furan-2-yl)­methanol (PD-HMF) into FDCA over the CeO 2 -supported Au catalyst, DFT calculations identify two crucial steps in the reaction mechanism, including the partial hydrolysis of the acetal into 5-formyl-2-furan carboxylic acid involving OH – and Lewis acid sites on CeO 2 , and subsequent oxidative dehydrogenation of the in situ generated hemiacetal involving Au nanoparticles …”
Section: Reaction Mechanism Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the rate-determining step or possible reaction pathway of reactions over CeO 2 -based catalysts can be identified by the reaction energy profiles via theoretical calculations. ,,,,, For example, during the oxidation of (5-(1,3-dioxan-2-yl) furan-2-yl)­methanol (PD-HMF) into FDCA over the CeO 2 -supported Au catalyst, DFT calculations identify two crucial steps in the reaction mechanism, including the partial hydrolysis of the acetal into 5-formyl-2-furan carboxylic acid involving OH – and Lewis acid sites on CeO 2 , and subsequent oxidative dehydrogenation of the in situ generated hemiacetal involving Au nanoparticles …”
Section: Reaction Mechanism Studiesmentioning
confidence: 99%
“…244 Additionally, the rate-determining step or possible reaction pathway of reactions over CeO 2 -based catalysts can be identified by the reaction energy profiles via theoretical calculations. 160,207,212,234,289,416 For example, during the oxidation of (5-(1,3-dioxan-2-yl) furan-2-yl)methanol (PD-HMF) into FDCA over the CeO 2 -supported Au catalyst, DFT calculations identify two crucial steps in the reaction mechanism, including the partial hydrolysis of the acetal into 5-formyl-2-furan carboxylic acid involving OH − and Lewis acid sites on CeO 2 , and subsequent oxidative dehydrogenation of the in situ generated hemiacetal involving Au nanoparticles. 110 To date, several studies have been reported theoretical calculations to predict the reaction products and explain experimental activity through estimating the adsorption and dissociation energies of reactants over CeO 2 -based catalysts, the energy profiles of intermediates, the interaction of CeO 2 support with the supported active species, and so on, which is helpful for understanding the reaction mechanism.…”
Section: Reaction Mechanism Studiesmentioning
confidence: 99%
“…96% propyne conversion . This intriguing catalytic performance of ceria has stimulated considerable research efforts to understand the mechanism for the selective hydrogenation of alkyne by both experimental ,− and computational studies. …”
Section: Introductionmentioning
confidence: 99%
“…31−33 Such SOMIs have been applied to a variety of oxide/metal inverse catalysts, such as ZnO/Au(111), 34 MgO/ Au(111), MgO/Ag(100), 14 TiO 2 /Au(111), 35 CeO 2 /Cu(111), 36 and CeO 2 /Ru(0001). 37 Among these, Au(111) has always been considered to be an ideal model for the growth of ultrathin FeO films due to its excellent reactivity and stability in the inverse catalysis process. 7,13 Because the atomic structures and properties of ultrathin oxide films are dramatically determined by the interfacial interactions, it is still essential to elucidate the growth mechanism and interface properties of the FeO/Au(111) system.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many reports about the epitaxial growth mode and the SOMIs of iron oxide films on various metal substrates have been published, showing excellent catalytic activity in various reactions. , For instance, monolayer FeO on Pt(111) is highly active, selective, and robust for CO oxidation at room temperature (RT) because of SOMI, which provides an effective method for designing active sites of catalysts . Similar to the FeO(111)/Pt(111) system, FeO/Pd(111) can also promote hydrogenation/dehydrogenation reactions and CO oxidation. Such SOMIs have been applied to a variety of oxide/metal inverse catalysts, such as ZnO/Au(111), MgO/Au(111), MgO/Ag(100), TiO 2 /Au­(111), CeO 2 /Au­(111), CeO 2 /Cu­(111), and CeO 2 /Ru­(0001) . Among these, Au(111) has always been considered to be an ideal model for the growth of ultrathin FeO films due to its excellent reactivity and stability in the inverse catalysis process. , Because the atomic structures and properties of ultrathin oxide films are dramatically determined by the interfacial interactions, it is still essential to elucidate the growth mechanism and interface properties of the FeO/Au(111) system. , Furthermore, a detailed understanding of the SOMI, how it affects the second layer metal oxide, needs to be extensively explored. , …”
Section: Introductionmentioning
confidence: 99%